"He's so Fluffy I'm Gonna Die!" Cute Responses by Hikers to Autonomous Animals on the Appalachian Trail. (2nd January 2019) - Marx, Kate
ABSTRACT: The Appalachian Trail is a more than 2, 000-mile-long wilderness trail in the Eastern United States. Every year, aspiring long-distance hikers travel from across the US and abroad, intending to hike the entire length of the trail, which takes around 6 months to complete. Numerous species of wildlife dwell on and around the trail. The aim of this study was to explore how long-distance hikers perceived the nonhuman animals that they encountered on their trek, and how they described navigating these encounters. Due to a thriving online community of hikers who blogged about their experiences on the trail, it was possible to retrieve a substantial amount of rich data detailing first hand encounters between hikers and animals on the trail. It was found that just under a third of all hiker narratives mentioning wild animals on the trail indicated that the author had responded to the animal as being cute. Despite cuteness frequently being perceived as trivial or banal, this paper argues that a hiker's perception of an animal as cute is more complex and meaningful to their overall experience of the animal than might initially be assumed. Both the aesthetic of cuteness and the effect of cuteness on an observer are considered in light of existing research on the subject. Some specific accounts of a hiker perceiving and responding to cuteness in animals on the trail are then explored, which leads on to a consideration of why so many animals on the trail might have been perceived as being cute. Finally, the paper discusses what being seen as cute meant for the animal involved, as hikers stared at, approached, followed, and frequently made attempts at touching or feeding animals that they found cute. The paper concludes that, far from being inconsequential, the perception of cuteness in an animal was meaningful for the human observer, as well as having consequences for the animal in question.